THE INFLUENCE OF COVID-19 EVENTS TO VACCINATION ON ABNORMAL RETURN AND TRADING VOLUME ACTIVITY IN IDX30 COMPANIES - Martina Rapolo Lumbantoruan; Harry Patuan Panjaitan; Teddy Chandra (Institut Bisnis dan Teknologi Pelita Indonesia, 2021)
The purpose of this study was to analyze how the market reacted to the covid-19 event that occurred in Indonesia, namely the existence of PSBB Volume I, New Normal, PSBB Volume II, the entry of the sinovac vaccine phase 1 to Indonesia, and the injection of the first vaccine to President Jokowi using abnormal returns and trading volume activity as an indicator of investor reaction in the capital market. In this study, there were 30 samples of IDX30 companies for the January 2021 period. To test investor reactions, an event study was used to measure the difference in reactions before and after the event. This study also used paired sample t-test for normally distributed data and the Wilcoxon sign rank test for data that were not normally distributed. The results of this study in the PSBB Volume I and New Normal events there was no abnormal return either before or after the event, in the PSBB Volume II event there was a positive abnormal return, 2 days before PSBB Volume II and negative abnormal returns 3 days after, in the event of the entry of the sinovac vaccine phase 1 into Indonesia, there was a negative abnormal return 2 days before the event, and in the event of the first vaccine injection to President Jokowi, there was a negative abnormal return 2 days before the event. However, there is no significant difference between abnormal returns before and after all events. While trading volume activity in the PSBB Volume I, New Normal, the entry of the sinovac vaccine phase 1 to Indonesia, and the first vaccine injection to President Jokowi, there was no difference between the activities before and after the event. But in the PSBB Volume II, there were significant differences in trading volume activity before and after the event.